Advancements in distributed computing and Internet technologies trends and issues - Pathan, Al-Sakib Khan; Pathan, Mukaddim; Lee, Hae Young (Information Science Reference, 2012)
"This book compiles recent research trends and practical issues in the fields of distributed computing and Internet technologies, providing advancements on emerging technologies that aim to support the effective design and implementation of service-oriented networks, future Internet environments and building management frameworks" - Provided by publisher
Includes bibliographical references
Keywords: Datenverarbeitung; Electronic data processing / Distributed processing; Service-oriented architecture (Computer science); Internet; Aufsatzsammlung